Power and ideology in Brazil - McDonough, Peter, 1939- (Princeton University Press, 1981)
Drawing on personal interviews with over 250 Brazilian leaders in industry, banking, politics, labor, the civil service, and the church, Peter McDonough challenges the conventional notion of elites in authoritarian regimes as unideological pragmatists. He demonstrates that the BrazilianOriginally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.